2015
DOI: 10.1371/journal.pone.0142599
|View full text |Cite|
|
Sign up to set email alerts
|

IL6 Inhibits HBV Transcription by Targeting the Epigenetic Control of the Nuclear cccDNA Minichromosome

Abstract: The HBV covalently closed circular DNA (cccDNA) is organized as a mini-chromosome in the nuclei of infected hepatocytes by histone and non-histone proteins. Transcription from the cccDNA of the RNA replicative intermediate termed pre-genome (pgRNA), is the critical step for genome amplification and ultimately determines the rate of HBV replication. Multiple evidences suggest that cccDNA epigenetic modifications, such as histone modifications and DNA methylation, participate in regulating the transcriptional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 38 publications
(52 reference statements)
4
54
1
1
Order By: Relevance
“…Belloni et al reported that interferon‐α treatment exhibited a direct antiviral effect in HBV‐infected PHHs by inducing hypoacetylation of cccDNA‐bound histones to decrease HBV transcript levels . Interleukin‐6 treatment in HBV‐infected HepG2‐NTCP cells led to a reduction of cccDNA‐bound histone acetylation paralleled by a rapid decrease in 3.5‐kb RNA and subgenomic RNAs . Riviere et al found that HBx recruitment to the cccDNA minichromosome serves to counteract chromatin‐mediated transcriptional repression established in part by histone methyltransferase SETDB, H3K9me3, and HP1 .…”
Section: Discussionsupporting
confidence: 59%
“…Belloni et al reported that interferon‐α treatment exhibited a direct antiviral effect in HBV‐infected PHHs by inducing hypoacetylation of cccDNA‐bound histones to decrease HBV transcript levels . Interleukin‐6 treatment in HBV‐infected HepG2‐NTCP cells led to a reduction of cccDNA‐bound histone acetylation paralleled by a rapid decrease in 3.5‐kb RNA and subgenomic RNAs . Riviere et al found that HBx recruitment to the cccDNA minichromosome serves to counteract chromatin‐mediated transcriptional repression established in part by histone methyltransferase SETDB, H3K9me3, and HP1 .…”
Section: Discussionsupporting
confidence: 59%
“…As Fig. 4d and e showed, expression of HNF1α, HNF4α and pgRNA was significantly decreased in response to SSc treatment, consistent with previous studies that IL-6 targets nuclear cccDNA minichromosome and inhibits cccDNA transcription [27].…”
Section: Ssc Downregulates Hnf1α and Hnf4α By Stimulating Il-6 Expressupporting
confidence: 90%
“…Virologic inhibition is a principal effect of the host immune response against HBV . We postulated that during chronic hepatitis repressed viral expression and the condensed architecture of cccDNA minichromosome may contribute to viral persistence.…”
Section: Resultsmentioning
confidence: 99%
“…During chronic hepatitis, antiviral immunity is functionally inefficient at eliminating viral persistence but has the potential to inhibit viruses . To simulate transcriptional repression, we took advantage of the site‐specific DNA‐binding capacity of Cre to recruit a KRAB repressive module to rcccDNA.…”
Section: Discussionmentioning
confidence: 99%